Ulangan 24:1-4: Hukum Perceraian atau Hukum Rujuk? - Yonky Karman (STT Reformed Injili Internasional, 2023)
The text of Deuteronomy 24: 1-4 is not as simple as it seems at first glance. It is often read as one, if not the only, divorce law in the Old Testament. Other interpreters read it as a law that protects wives from arbitrary divorce. This article and several other interpreters disagree with these two interpretations. What makes this article different is the use of modern legal discourse. Based on the legal subject and legal relationship, this text prohibits a husband from reuniting with his ex-wife whom he has divorced and who has also remarried to another man and then became a widow again. To interpret the original intent of this law, it would parallelise contemporaneous or more ancient extrabiblical sources, but none are found. Its postbiblical parallels are found in a Jewish legal text and a Quranic text, which confirms the text of Deuteronomy as a prohibition of marriage reunion. It helps us read Deuteronomy's text as a prohibition of (marriage) reunion. This law is for husbands with a strong position in a patriarchal culture so they do not arbitrarily divorce their wives because their regret would be useless.